Highly stable dual-phase Y0.8Ca0.2Cr0.8Co0.2O3-Sm0.2Ce0.8O1.9 ceramic composite membrane for oxygen separation - Yoon, Kyung Joong; Marina, Olga A. (ELSEVIER SCIENCE BV, 2016)
A highly stable ceramic composite membrane composed of Ca- and Co-doped yttrium chromite, Y0.8Ca0.2Cr0.8Co0.2O3 (YCCC), and samaria-doped ceria, Sm0.2Ce0.8O1.9 (SDC), was demonstrated for oxygen separation. Homogeneously dispersed nano-scale composite powders were synthesized by a single-step combustion process based on the glycine-nitrate method. Dense composite membranes were achieved having submicron grain sizes and well-percolated electronic and ionic conduction pathways. Densification of the composite membrane was assisted by liquid phase sintering caused by cobalt-doping in yttrium chromite, and gas-tight membranes are fabricated at 1400 degrees C. The YCCC and SDC phases were chemically and thermo-mechanically compatible at both processing and operating temperatures. The composite membrane exhibited an oxygen permeation flux comparable to those of the state-of-the-art single-phase membrane materials and excellent stability in harsh operating conditions under a H-2-CO2 environment for long-term operation, which suggests potential application in various combustion and fuel production processes. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: HOLLOW-FIBER MEMBRANE; THERMAL-EXPANSION; ELECTRICAL-PROPERTIES; STABILIZED ZIRCONIA; AC-IMPEDANCE; PERMEATION; PERMEABILITY; PEROVSKITE; SEMIPERMEABILITY; CE1-XSMXO2-X/2